Multi-scale analysis of environmental constraints on macrophyte distribution, floristic groups and plant diversity in the Lower Paraná River floodplain - Morandeira, Natalia Soledad (2015)
The Paraná River floodplain comprises one of the largest wetland systems of South America. In a sector of the Lower Paraná River floodplain (100km length, 3650km2), floristic composition and species diversity was characterized in 88 sites surveyed during summers 2010-11 and 2011-12. Hierarchical and fuzzy classifications were used to construct 26 floristic groups and 8 associations of floristic groups, and their indicator species were identified. A number of 124 species was distributed with a zonation pattern conforming marshes, salt marshes, wet prairies, bunchgrasses, grasslands and scrublands. We assessed how vegetation is affected by four nested levels of environmental constraints, representing a gradient from a landscape to a local scale, and including hydrological, geomorphological, topographic and edaphic variables. Species richness differed within categories of broad-scale landscape units (level 1) and within topographic positions (level 3). Also, 30 plant species, six floristic groups and five associations of groups responded to levels 1-3. The first two axes of a constrained Outlying Mean Index ordination accounted for 60% of the marginality of 61 common species as a function of soil features and flood frequency (level 4). Thus, the distribution of seven species showed significant marginality in association to soil electrical conductivity, soil silt percent and soil total nitrogen concentration. Multi-scale environmental constraints determined vegetation zones, and emerging floristic and diversity patterns. The multi-scale approach significantly improves the understanding of floristic patterns and plant biodiversity in the study area, and may be extended to other floodplain wetlands.